OC-025 The first report of the UK multicentre double balloon enteroscopy registry: broadening the international deep enteroscopy experience. (23rd September 2015) - Despott, E J; Hughes, S; Deo, A; Sanders, D S; Sidhu, R; Willert, R; Plevris, J; Trimble, K; Jennings, J; Fraser, C
Abstract : Introduction: Double balloon enteroscopy (DBE) has been a pivotal endoscopic technology, transforming the investigation and management of small bowel (SB) disorders by facilitating direct endoscopic access of the entire small bowel. Methods: We report the initial experience of the UK multicentre registry (six centres) since the introduction of DBE in the UK in 2005. Results: 550 cases (322 men) were performed. Mean age was 56 years (16–94 years). 189 cases were done under general anaesthesia, 361 cases done under conscious sedation. 372 cases were performed via the oral route, 175 were performed via the rectal route while three cases were performed via an ileostomy. Calculated mean depth of insertion was 270±80 cm and 190±75 cm for oral and rectal routes, respectively. Mean time taken to complete procedures was 74±20 min. Carbon dioxide was used as the insufflating gas in 344 cases while air was used in the remaining 206 cases. DBE was preceded by capsule endoscopy (CE) in 403 cases. Concordance of diagnoses at CE and DBE was 66% and the overall diagnostic yield for DBE was 61%. The indications and therapies applied at DBE are shown (Abstract 025 ). Significant lesions missed by CE but diagnosed by DBE included large vascular lesions, polyps and other small bowel tumours. Endoscopic therapy at DBE was applied in 38% of procedures. There were three reported complications (2 perforations and 1 acute coronary syndrome); all complications occurred during therapeutic procedures. The overall complication rate for DBE in the series was 0.5%, with a complication rate for therapeutic procedures of 1.4%. There were no cases of acute pancreatitis. Limitations to DBE procedures included patient intolerance, the presence of adhesions and poor bowel preparation. Conclusion: The initial UK experience is favourable and echoes the results of other national series published to date, showing that DBE is a feasible and safe and endoscopic advancement that enhances the management of small bowel disorders.